Evaluating Use Cases for Human Challenge Trials in Accelerating SARS-CoV-2 Vaccine Development. (6th July 2020) - Nguyen, Linh Chi; Bakerlee, Christopher W; McKelvey, T Greg; Rose, Sophie M; Norman, Alexander J; Joseph, Nicholas; Manheim, David; McLaren, Michael R; Jiang, Steven; Barnes, Conor F; Kinniment, Megan; Foster, Derek; et al.
Abstract: Human challenge trials (HCTs) have been proposed as a means to accelerate SARS-CoV-2 vaccine development. We identify and discuss 3 potential use cases of HCTs in the current pandemic: evaluating efficacy, converging on correlates of protection, and improving understanding of pathogenesis and the human immune response. We outline the limitations of HCTs and find that HCTs are likely to be most useful for vaccine candidates currently in preclinical stages of development. We conclude that, while currently limited in their application, there are scenarios in which HCTs would be extremely beneficial. Therefore, the option of conducting HCTs to accelerate SARS-CoV-2 vaccine development should be preserved. As HCTs require many months of preparation, we recommend an immediate effort to (1) establish guidelines for HCTs for COVID-19; (2) take the first steps toward HCTs, including preparing challenge virus and making preliminary logistical arrangements; and (3) commit to periodically re-evaluating the utility of HCTs. Abstract : Despite limitations, human challenge trials could accelerate a SARS-CoV-2 vaccine by providing signals of vaccine efficacy in as little as 2 months or by identifying surrogates of protection. Trial preparations would take many months and hence should be started immediately.